Building Vocabulary Items: Having Fun in Playing Vocabulary Mastery Using Snakes and Ladders Board Game - Lende, Olviana; Sari, Ike Dian Puspita; Fitriani, Enis (UIBU, 2024)
This study aimed to increase the students' vocabulary by using snakes and ladders board media in grade 7 SMP N 3 Ombarade West Sumba Data. The research subjects were a class consisting of 15 grade VII students of SMP N 3 Ombarade Sumba Barat Daya for the 2023 academic year. This research was conducted by using the R&D method. Data collection techniques were obtained from observation sheets, interviews, and photographic evidence. The results of this study indicated an increase in the results of media experts 83.33% and material expert results 91.67%. This shows that increasing students' vocabulary through snakes and ladders game can improve students' learning abilities. vocabulary mastery and can affect student achievement in vocabulary mastery. Therefore it can be concluded that increasing students' vocabulary through snakes and ladders game is effective in increasing students' interest in participating in the teaching and learning process.